Toán Lớp 8: 1/ x ² -2x+1-y ² 2/ x ²-2xy+y ²- 9z ² 3/ x ²-4xy +4y ²-z ²+4zt -4t ² 4/ a^4 -ax ³ -ay+xy 5/ x ² +2x+1-y ² 6/ x ² + 2xy +y ²- 4z ² 7/ x

Question

Toán Lớp 8: 1/ x ² -2x+1-y ²
2/ x ²-2xy+y ²- 9z ²
3/ x ²-4xy +4y ²-z ²+4zt -4t ²
4/ a^4 -ax ³ -ay+xy
5/ x ² +2x+1-y ²
6/ x ² + 2xy +y ²- 4z ²
7/ x ²-2xy +y ² -z ² +2zt – t ²
8/ a ³ -ax ² -ay +xy, hướng dẫn giải giúp em bài này ạ, em cảm ơn thầy cô và các bạn nhiều.

in progress 0
Kỳ Anh 2 tháng 2022-12-22T17:59:21+00:00 2 Answers 0 views 0

TRẢ LỜI ( 2 )

  1. 1. x^2-2x+1-y^2
    = (x-1)^2-y^2
    = (x-1-y)(x-1+y)
    2. x^2-2xy+y^2-9z^2
    = (x-y)^2-9z^2
    = (x-y-3z)(z-y+3z)
    3. x^2-4xy+4y^2-z^2+4zt-4t^2
    = (x^2-4xy+4y^2)-(z^2-4zt+4t^2)
    = (x-2y)^2-(z-2t)^2
    = (x-2y-z+2t)(x-2y+z-2t)
    4. a^4-ax^3-ay+xy
    = x(a^3-x^3)-y(a-x)
    = x(a-x)(a^2+ax+x^2)-y(a-x)
    = x(a-x)(a^2+ax+x^2-y)
    5. x^2+2xy+1-y^2
    = (x+1)^2-y^2
    = (x+1-y)(x+1+y)
    6. x^2+2xy+y^2-4z^2
    = (x+y)^2-4z^2
    = (x+y-2z)(z+y+2z)
    7. x^2-2xy+y^2-z^2+2zt-t^2
    = (x^2-2xy+y^2)-(z^2-2zt+t^2)
    = (x-y)^2-(z-t)^2
    = (x-y-z+t)(x-y+z-t)
    8. a^3-ax^2-ay+xy
    = a(a^2-x^2)-y(a-x)
    = a(a-x)(a+x)+y(a-x)
    = a(a-x)(a+x+y)

  2. Giải đáp+Lời giải và giải thích chi tiết:
     1, x² – 2x + 1 – y²
    = (x – 1)² – y²
    =(x – 1 – y ).(x – 1 + y)
    2, x² – 2xy + y² – 9z²
    = (x – y)² – 9z²
    = (x – y – 3z).(x – y + 3z)
    3, x² – 4xy + 4y² – z² + 4zt – 4t²
    = (x² – 4xy + 4y²) – (z² – 4zt + 4t²)
    =( x – 2y)² – (z – 2t)²
    = (x – 2y – z + 2t).(x – 2y + z – 2t)
    4, $a^{4}$ – ax³ – ay + xy
    = a(a³ – x³) – (ay – xy)
    = a.(a- x).(a² + ax +x²) – y(a – x)
    = (a – x).(a³ + a²x + ax² – y)
    5, x² + 2x + 1 – y²
    = (x + 1)² – y²
    = (x + 1 – y).(x + 1 + y)
    6, x² + 2xy + y² – 4z²
    =(x + y )² – 4z²
    = (x + y – 2z).(x + y + 2z)
    7, x² – 2xy + y² – z² + 2zt – t²
    = (x² – 2xy + y²) – (z² – 2zt + t²)
    = (x – y)² – (z – t)²
    = (x – y + z – t).(x – y – z  + t)
    8, a³ – ax² – ay + xy
    = (a³ – ax² ) – (ay – xy)
    = a(a² – x²) – y(a – x)
    = a(a – x).(a + x) – y(a – x)
    =(a – x).(a² + ax – y)

Browse

12:2+4x4-12:2-5x3 = ? ( )